Logs for acid-base chemistry: illustrating the potential of multidisciplinary learning support interventions from the third space - Joshua Wang; Elise Kenny (Journal of Learning Development in Higher Education)
The growing accessibility of higher education over the last century is a major accomplishment and should be continuously supported. A particular barrier to widening participation is that curricula across numerous disciplines rely on assumed knowledge for enrolling students.  The gaps between this assumed and actual pre-existing knowledge are dispersed throughout institutions, making them difficult to bridge. Our institution runs seven different first-year chemistry subjects, all of which require students to use mathematical logarithms to solve acid-base chemistry problems.  Our case study illustrates that third space practitioners with disciplinary expertise, such as those working in STEM support for learning, are uniquely positioned to address challenges like this.  As a chemistry educator and mathematics educator employed in the third space, we co-designed and co-delivered a one-hour online workshop titled “logs for acid-base chemistry”. The session explicitly taught logarithmic concepts in context to students from four different chemistry units. Observations made during the workshop suggest that the intervention was able to efficiently improve acid-base calculation confidence in students from all attending cohorts.  Finally, the broader benefits of subject specialist third space staff in higher education are discussed in light of the case study findings. Overall, the efficiency of this intervention highlights the under-researched potential of embedding disciplinary experts in third space learning support roles.